Reviewing shariah certificates of DSN MUI (a study on shariah certificate of DSN MUI on Paytren) - Muh Nashirudin; Millatus Sa'adah (Ijtihad : Jurnal Wacana Hukum Islam dan Kemanusiaan, 2019)
MUI (Majelis Ulama Indonesia/ Indonesian Ulema Council) has issued a fatwa which is related to Multi Level Marketing. This fatwa number 75/VII/ 2009 concerns with Sharia Multistage Direct Selling (PLBS) that requires an MLM company to fulfill twelve regulations  to be categorized as sharia law-conformed and deserve to get a sharia business certificate. However, DSN-MUI has also issued a decree number No. KEP- 03/DSN-MUI/VII/ 2016 on the list of sharia multistage direct selling companies and includes PT Veritra Santosa Internasional (VSI), which has sold Paytren application, as a sharia MLM with a decree number SK: 010.57.01/DSN-MUI/VII/2017. This study will discuss the consistency of DSN-MUI with its fatwa by analyzing the conformity between certficate of halal or sharia issued by DSN-MUI on Paytren and the fatwa of DSN-MUI on PLBS.